Environmental Factors as Contributors to Sleep Disturbance in Critically Ill Patients in Intensive Care Units (ICU): A Descriptive Study - Rustam, Junaidy Suparman; Chaidir, Reny (Majalah Anestesia & Critical Care, 2024)
Background: Sleep disturbance is a common problem among critically ill patients in the ICU and can significantly affect their overall experience of care. This study aims to study the experience of sleep disturbance in critically ill patients in the ICU. Methods: This study was conducted in a public hospital in West Sumatra, Indonesia from June to August 2022, using a descriptive approach and focusing on a population of critically ill patients admitted to the ICU. The sample size of 80 participants was determined using power analysis from previous studies, and sampling was done using purposive technique based on inclusion criteria. Results: The results of this study showed that 37.5% of participants reported experiencing sleep disturbances while being treated in the ICU. This demonstrates the prevalence of problems experienced by critically ill patients and highlights the need for targeted interventions to address them. It is imperative for healthcare providers to recognize the impact of sleep disturbances on patient health and recovery and implement strategies to reduce their impact. Conclusion: This study showed a significant prevalence of sleep disturbance among critically ill patients in the ICU. This underscores the importance of proactive measures to address this issue and emphasizes the role of healthcare facilities in providing support and education to individuals affected by sleep disturbance. Further research and appropriate interventions need to be conducted to improve the sleep quality of critically ill patients in the ICU contributing to better overall outcomes and quality of care in the ICU.